Self efficacy dalam penggunaan kondom pada Lelaki Seks Lelaki (LSL) dengan HIV/AIDS: Literature review - Nirwanto K Rahim; Sri Yona; Agung Waluyo (Holistik Jurnal Kesehatan, 2020)
Self-efficacy for condom use related sexual risk behavior among men who have sex with men and HIV/AIDS: A literature reviewBackground: The prevalence of HIV / AIDS in the world is increasing. Men who have sex with men  (MSM) is the population most vulnerable to HIV / AIDS. Transmission occurred  because of the low use of condoms. Self-efficacy is the ability to belief of self against individual coping in specific situations that affect thinking, behavior, and emotional patterns that can affect attitudes in controlling motivation, behavior, social and the surrounding environmentPurpose: A literature study was explore self-efficacy in using condom and measurement of self-efficacy in condom useMethod: Literature studies used the online database Proquest, CINAHL, the literature was limited by criteria: in 2016-2019, full text and English language, with the keywords: "Self-Efficacy AND Condom Use", "HIV / AIDS AND MSM," HIV / AIDS AND Self EfficacyResults: Finding 9 articles that were relevant to the inclusion criteria. The results showed that there were  two categories in the assessment of self-efficacy in HIV / AIDS patients, namely Sexual Self-Efficacy, and Condom Self-EfficacyConclusion: The assessment used several different instruments, however, although the instruments used were different in the assessment of self-efficacy,  the results of the entire study showed  a link between self-efficacy in the use of condoms in MSM. The results of this literature review can be used as information material about the importance of self efficacy in improving the consistency of condom use to prevent HIV / AIDS Keywords: HIV/AIDS; Self-Efficacy, Condom Use; Sexual risk; BehaviorPendahuluan: Prevalensi HIV/AIDS di dunia semakin meningkat. Lelaki seks lelaki (LSL ) merupakan populasi yang paling mudah terkena HIV/AIDS. Penularan terjadi karena rendahnya penggunaan kondom. Self-efficacy merupakan kemampuan untuk percaya pada kemampuan diri terhadap koping individu dalam situasi yang spesifik yang mempengaruhi pemikiran, perilaku, dan pola emosional yang dapat berdampak pada sikap dalam mengontrol motivasi, perilaku, dan sosial serta lingkungan sekitar.Tujuan: Untuk mengeksplorasi  self-efficacy  dalam penggunaan kondom dan pengukuran self-efficacy dalam penggunaan kondom.Metode: Studi literatur melalui database online Proquest, CINAHL,  literature dibatasi dengan kriteria : tahun 2016-2019, full text dan berbahasa Inggris, dengan kata kunci: “Self-Efficacy AND Condom Use”,“HIV/AIDS AND MSM,”HIV/AIDS AND Self EfficacyHasil: Didapatkan self-efficacy pada pasien HIV/AIDS dibedakan menjadi Sexual Self- Efficacy, dan Condom Self-Efficacy dan penilaian menggunakan beberapa instrument yakni  sexual self-efficacy scale, the AIDS-Prevention Self-efficacy Scal, condom use self-efficacy, condom use self-efficacy scale,Simpulan: terdapat  instrumen yang berbeda namun, meskipun instrumen yang digunakan berbeda dalam penilaian self-efficacy namun seluruh hasil penelitan menunjukkan adanya keterkaitan self-efficacy dalam penggunaan kondom pada LSL. Hasil telaah literature ini dapat dijadikan bahan informasi tentang pentingnya self efficacy dalam meningkatkan konsistensi penggunaan kondom untuk mencegah HIV/AIDS.